2001
DOI: 10.1029/2001jd900048
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of water vapor in the lower stratosphere observed in Halogen Occultation Experiment data

Abstract: Abstract. The seasonal cycle of water vapor in the lower stratosphere is studied based on Halogen Occultation Experiment (HALOE) satellite observations spanning 1991-2000. The seasonal cycle highlights fast, quasi-horizontal transport between tropics and midlatitudes in the lowermost stratosphere (near isentropic levels -380-420 K), in addition to vertical propagation above the equator (the tropical "tape recorder"). The rapid isentropic transport out of the tropics produces a layer of relatively dry air over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
179
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(204 citation statements)
references
References 57 publications
(18 reference statements)
24
179
1
Order By: Relevance
“…The additional effect of upward transport in the lower-stratospheric Brewer-Dobson circulation creates the well-known water vapour tape recorder signal (e.g. Mote et al, 1996;Randel et al, 2001). Note that the larger annual temperature cycle at 70 hPa (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The additional effect of upward transport in the lower-stratospheric Brewer-Dobson circulation creates the well-known water vapour tape recorder signal (e.g. Mote et al, 1996;Randel et al, 2001). Note that the larger annual temperature cycle at 70 hPa (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Latitude vs. log (Pressure) plots. downwards and polewards suggesting quasi horizontal transport in the lowermost stratosphere as discussed in Randel et al (2001). The gradients above 50 hPa indicate a much more horizontally isolated tropical stratosphere at these levels.…”
Section: Lower Stratospheric Water Vapor and Zonal Windsmentioning
confidence: 90%
“…HALOE is validated against other stratospheric water vapor measurements in the Stratospheric Processes and Their Role in Climate (SPARC) water vapor assessment study (WMO 2000). The HALOE instrument has been widely used for water vapor studies such as in the works of: Mote et al (1996); Rosenlof et al (1997); Considine et al (2001); Randel et al (2001);Geller et al (2002);and Gettelman et al (2002). We obtained the data from the SPARC Reference Climatology Project (randel@ucar.…”
Section: Observations and Reanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Randel et al [2001] analyzed the water vapor mixing ratio of 390 K isentropes that nearly corresponds to the tropopause based on Halogen Occultation Experiment satellite data. They showed that a water vapor minimum region in January exists on the northern side of the equator (centered at 10°-20°N) in longitudinal sections including Indonesia.…”
Section: Latitudinal and Longitudinal Structurementioning
confidence: 99%